Forearm Deoxyhemoglobin and Deoxymyoglobin (Deoxy[Hb + Mb]) Measured by Near-Infrared Spectroscopy (NIRS) Using a Handgrip Test in Mitochondrial Myopathy. Issue 3 (March 2015) - Celie, Bert M.; Boone, Jan; Smet, Joél E.; Vanlander, Arnaud V.; De Bleecker, Jan L.; Van Coster, Rudy N.; Bourgois, Jan G.
The purpose of this paper is to test whether peripheral oxygenation responses measured with near-infrared spectroscopy (NIRS) would differ between patients suffering from mitochondrial myopathy (MM) and healthy controls during an incremental handgrip exercise test. Two groups of subjects were studied: 11 patients with MM and 11 age- and gender-matched untrained healthy controls. A handgrip exercise until exhaustion protocol was used consisting of 2 min periods of work (Hz) at different intensities, separated by a 60 s rest period. The changes in deoxyhemoglobin and deoxymyoglobin (deoxy[Hb + Mb]) during each work step were expressed in percent to the maximum deoxy[Hb + Mb]-value measured during arterial occlusion in forearm muscles. A repeated measures analysis of variance was used to compare the increase in deoxy[Hb + Mb] between MM patients and controls with increasing intensity. Statistical analysis revealed a significant difference between both populations ( P < 0.001) indicating that the increase in deoxy[Hb + Mb] showed a significantly different pattern in the two populations. In the post hoc analysis significant lower deoxy[Hb + Mb] -values were found for MM patients at every intensity. The results of this paper show significantly different skeletal muscle oxygenation responses, measured with an optical method as NIRS, between MM patients and age- and gender-matched healthy subjects at submaximal and maximal level during an incremental handgrip exercise. This optical method is thus a valuable tool to assess differences in peripheral oxygenation. Moreover, this method could be used as an evaluation tool for follow up in interventional pharmacological studies and rehabilitation programs.